2014
DOI: 10.4028/www.scientific.net/msf.789.100
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Cotton Fiber/Poly(lactic acid) Composites

Abstract: In order to improve the mechanical properties of poly (lactic acid) (PLA), cotton fiber/PLA composites were prepared by melting compounding and injection molding. The effects of cotton fiber content and coupling agent on mechanical properties, crystalline behavior and interface morphology of the composites were studied by universal testing machine, DSC and SEM, respectively. The results showed that the crystallinity of the composites increased gradually with the increase of cotton fiber content, whereas the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to research, CF-reinforced thermoplastic composites have remarkable mechanical properties and are finding increasing applications in the automotive and medical fields 2,27 . Qian et al 28 manufactured a CF-reinforced composite with a polylactic acid (PLA) matrix. The composite containing 20% CF has the best mechanical properties according to the findings.…”
Section: Cfrpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research, CF-reinforced thermoplastic composites have remarkable mechanical properties and are finding increasing applications in the automotive and medical fields 2,27 . Qian et al 28 manufactured a CF-reinforced composite with a polylactic acid (PLA) matrix. The composite containing 20% CF has the best mechanical properties according to the findings.…”
Section: Cfrpcsmentioning
confidence: 99%
“…Effect of cotton fibre (CF) content on (a) tensile (b) flexural and (c) impact properties of CF/ polylactic acid (PLA) composites 28 .…”
Section: Cfrpcsmentioning
confidence: 99%
“…The impact resistance strengths of the composites exceeded those of PLA, and thermogravimetric analysis showed that the alkali pretreatment enhanced the thermal stability of the composites. Qian et al [ 20 ] prepared cotton fiber/PLA composites using melt-blending and injection-molding methods and investigated the effects of different fiber content and lengths. The results indicated that the tensile strength and elastic moduli of the composite were maximized at a fiber content of 20 wt%, and they increased by 35.7% and 44.9%, respectively, compared with those of pure PLA.…”
Section: Introductionmentioning
confidence: 99%